PENGARUH SIKAP KONSUMEN, PERSEPSI HARGA, PENDISTRIBUSIAN PRODUK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE SAMSUNG ANDROID (StudiEmpirisPadaMahasiswaFakultasEkonomikadanBisnis UniversitasStikubank Semarang) (Students' Journal of Economic and Management, 2015)
The Purpose of this reseach is to determine the effect of consumer attitudes, perception price, product distribusian, and product quality are shared or partially on purchasing decisions Samsung Android phone. The data used in this study is primary data, the questionnaire as a research instrument, which is then processed by the calculation SPSS (Statistical Product and Solutions) version 19. The population in this study is the faculty of economics and bussines students who use mobile phone Samsung android in university Stikubank Unisbank Semarang. Samples taken is the faculty of economics and bussiness students who use mobile phone Samsung Android in university Stikubank Unisbank Semarang, totaling 100 respondents. Sampling techniques in this study using a purposive sampling, ie deliberate sampling in accordance with the requirements of sample is required. Analysis tool used is multiple linear regression. The results showed that there is a significant positive effect between consumer attitudes toward purchasing decisions. There is a significant positive effect of perception price on purchase decisions. There is a significant positive effect between the product distribution to the purchasing decision. There is a significant positive effect between good quality product to the purchasing decision. Keywords:Consumer attitudes, perception price, product distribution, product quality, and purchase decisions.